Does Plasmodium Infection Affect Mosquito Attraction? - Santiago-Alarcon, Diego; Ferreira, Francisco C. (Frontiers in Ecology and Evolution, 2020)
Vector-host interactions play a central role in the transmission of vector-borne diseases. Determining the factors that affect vector attraction to vertebrate hosts is critical to understand disease ecological dynamics. Using malaria as the primary model, we reviewed studies that examined whether pathogen infection and host traits affect mosquito attraction. We found contradictory results examining mosquito attraction to birds infected with Plasmodium parasites, presumably because of widely variable experimental approaches. We summarize current experimental findings and propose standardized experimental approaches for future studies.